System Biology Approaches to Identify Biomarker in Liver Diseases - Arya, Vikram; Patra, Biswanath (International Journal of Bio-resource and Stress Management, 2023)
System biology emerging from year 2000 onwards in biomedical sciences is multi disciplinary approaches focus on complex dynamics interaction with in biological system. Alcohol and other drugs are potent cause of liver failure in USA and Worldwide. We describe system biology approaches a potential tool for identifying cell signaling pathways and co expressed genes involved in liver toxicity induced by reactive oxygen species, free fatty acids, and TNFα in liver hepatocyte, kupffer cell and stellate cells. System biology approaches analyzed multiple omics data i.e. Phenomics, Genomics, Epigenomics, Lipidomics, Metabolomics, Transcriptomics and Proteomics etc. to understand gene expression, metabolic profile, toxicity profile to predict and validate or characterized gene targets for liver toxicity.